2016
DOI: 10.5812/ircmj.39860
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of Manual Handling of Patients and Its Relationship with the Prevalence of Musculoskeletal Disorders Among Nursing Staff: Performance Evaluation of the MAPO and PTAI Methods

Abstract: Background: Manual handling of patients without using proper devices built for this purpose is the most important risk factor causing musculoskeletal disorders (MSDs) among nursing staff. Objectives: The aim of the present study was to determine the prevalence of MSDs, assess the risk of manual handling of patients, and identify the risk factors related to the development of such disorders among nursing staff. Methods: This cross-sectional study was conducted in 2015 and included 220 nurses from 24 wards who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
1
10
2
Order By: Relevance
“…Akbari et al. () in Iran found that increase in body mass index (BMI) and nurse‐to‐bed ratio could be a risk factor for BPPHTs. Nurse‐to‐bed ratio, as an index for physical workload, can increase the prevalence of back pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akbari et al. () in Iran found that increase in body mass index (BMI) and nurse‐to‐bed ratio could be a risk factor for BPPHTs. Nurse‐to‐bed ratio, as an index for physical workload, can increase the prevalence of back pain.…”
Section: Discussionmentioning
confidence: 99%
“…A US study including 15 national monitoring systems for healthcare workers and 45 hospital exposure prevention programs estimated that the number of percutaneous injuries in healthcare providers was annually 384,325 cases (Panlilio et al., ). In addition, trips, slips and falls cause a high rate of lost‐workday injuries (Bell et al., ) and patient handling plays a key role in back injuries among nurses (Akbari, Akbari, & Abadi, ). Working and organisational conditions are factors potentially involved in the occurrence of occupational injuries (García‐Herrero et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Rahimi 37 2015 Hamedan back pain scale Dehdashti 38 2015 Damghan Nordic Questionnaire Dadarkhah 39 2013 Army Hospital Nordic Questionnaire Choobin 21 2007 Shiraz Nordic Questionnaire Khoshbakht 40 2011 Rasht REBA tool Barzideh 17 2013 Shiraz Nordic Questionnaire Imanzad 22 2013 Ghom Nordic Questionnaire Mehdipour 41 2012 Ghazvin Nordic Questionnaire Rezai 42 2014 Tehran questions about LBP and its risk factors Choobin 43 2010 Shiraz Nordic Questionnaire Bandpei 44 2006 North Of Iran Self-made questionnaire Farahabadi 45 2016 Ghom Nordic Questionnaire Arsalani 3 2016 Tehran working conditions and MSDs Farokhi 46 2016 Esfahan Nordic Questionnaire Nikpour 47 2009 Tehran Nordic Questionnaire Sadeghiyan 48 2005 Shahroud Nordic Questionnaire Asadi 49 2016 Rasht information on the status of skeletal pain Raeisi 50 2011 Tehran Nordic Questionnaire Akbari 51 2015 Tehran Nordic Questionnaire Taghinejad 52 2016 Ilam Nordic Questionnaire Samaei 53 2014 Kerman List of MAPO and PTAI Zamanian 54 2015 Shiraz Nordic Questionnaire Table 2 The results of meta-analysis to combine the prevalence of Musculoskeletal Disorders in Nurses. The present research reviewed the studies that investigated the prevalence of musculoskeletal disorders in Iranian nurses working in hospitals during the period from April 2000 to April 2017 in Persian and English domestic and foreign language journals.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, Patient Transfer Assessment Instrument (PTAI) is an objective method for assessing the load of patient handling that was introduced in 2005 and revised in 2007 [28]. PTAI can be used for evaluation of the ergonomic working postures and the workers' skills during patient handling [29].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation method was carried out by observing 15 factors in which nine factors can be investigated by the assessor's observation of how subjects work, and the last six factors can be assessed based on workers' interviews [27,29].…”
Section: Introductionmentioning
confidence: 99%